UJI AKTIVITAS ANTIOKSIDAN SEDIAAN SIRUP DAUN SEREH (Cymbopogon citratus) - dina febrina (Universitas Harapan Bangsa Purwokerto, 2018)
ABSTRACT Antioxidants are compounds that can inhibit reactive oxygen species and also free radicals so that antioxidants can prevent diseases associated with free radicals such as carcinogenesis, cardiovascular, and aging. The emergence of a negative response to the use of synthetic antioxidants is thought to have the potential to cause cancer. So that natural antioxidants are increasingly in demand because they are believed to be safer for health. Lemongrass (Cymbopogon citratus) is one of the plants commonly used as spices by the people of Indonesia. Determination of antioxidant activity of lemongrass syrup was carried out by DPPH method. the results showed an IC50 value of lemongrass syrup preparations of 50.68 ppm.